Do sagrado ao profano: transformações fúnebres na cidade de São Paulo - 1858 -1890 - Pereira, Thais Cristina (2018)
This dissertation deals with changes in funerary customs in the city of São Paulo between 1858 and 1890. After much discussions, in 1858 was inaugurated the first public cemetery of the capital of São Paulo: the Consolation. This edification made possible the construction of other necropolises in the city. The existence of these new public spaces has brought the development of services and funerals companies, commercial activity that was source of much controversy, because for many people, it was an immoral trade. The funeral customs of traditional Catholicism, linked to the sacred, had to adapt to hygienist discourses and specific legislation to advance in the project of desacralization of the rites and spaces of death